Nonalcoholic fatty liver disease: histopathological evaluation and interobserver agreement Doença hepática gordurosa não-alcoólica: avaliação histopatológica e concordância interobservador - Cynthia Koeppel Berenstein; Caroline Guimarães Cardoso; Nivaldo Hartung Toppa; Virginia Hora Rios Leite (Sociedade Brasileira de Patologia Clínica, 2008)
BACKGROUND: Nonalcoholic fatty liver disease comprises a spectrum of lesions ranging from steatosis to cirrhosis, with nonalcoholic steatohepatitis being the progressive form of the disease. Alcohol intake, viral hepatitis and other liver diseases must be excluded. Liver biopsy is the gold standard for diagnosis of the disease and is the only method able to differentiate nonalcoholic steatohepatitis from simple steatosis, to grade inflammation and to stage fibrosis. AIMS: To analyze the histopathological findings and evaluate interobserver agreement in biopsies previously diagnosed as steatosis or steatohepatitis. METHODS: Seventy needle biopsies were analyzed according to Brunt et al.(4), with modifications in the grading and staging components. Clinical data of patients were collected. Interobserver agreement was calculated based on histopathological findings. RESULTS: Mild nonalcoholic steatohepatitis (grade 1) was the most common form. If fibrosis was detected, stage 1 was the most frequent. Interobserver agreement was very good for macrovesicular steatosis (K W = 0,82) and good for lobular inflammation (K W = 0,68) and fibrosis (K W = 0,73). CONCLUSIONS: The classification of Brunt et al., with modifications, can be applied to diagnosis not only of nonalcoholic steatohepatitis but also of nonalcoholic fatty liver disease, representing a reliable method for use in the daily practice of pathologists. INTRODUÇÃO: A doença hepática gordurosa não-alcoólica compreende um espectro de lesões que variam da esteatose à cirrose, sendo a esteatoepatite não-alcoólica a forma progressiva da doença. Uso de álcool, hepatites virais e outras doenças hepáticas devem ser excluídos. A biópsia hepática é o padrão-ouro para o diagnóstico da doença, sendo o único método capaz de diferenciar a esteatoepatite da esteatose, graduar a inflamação e estadiar a fibrose. OBJETIVOS: Analisar os achados histopatológicos e avaliar a concordância interobservador em biópsias previamente diagnosticadas como esteatose ou esteatoepatite. MATERIAIS E MÉTODOS: Setenta biópsias por agulha foram analisadas segundo Brunt et al.(4), com modificações nos componentes determinantes da atividade e no estadiamento. Os informes clínicos dos pacientes foram coletados. A concordância interobservador foi calculada com base nos achados histopatológicos. RESULTADOS: Esteatoepatite não-alcoólica discreta (grau 1) foi a forma mais comum. Se havia fibrose, o estágio 1 foi o mais freqüente. Concordância interobservador foi muito boa para esteatose macrovacuolar (KW = 0,82) e boa para inflamação lobular (KW = 0,68) e fibrose (KW = 0,73). CONCLUSÕES: A classificação de Brunt et al., com modificações, pode ser usada para o diagnóstico não somente da esteatoepatite não-alcoólica, mas também da doença hepática gordurosa não-alcoólica, representando método confiável para uso na rotina diária dos patologistas.